Student Support in Open Learning: Sustaining the process - Dearnley, Christine (International Review of Research in Open and Distributed Learning, 2003)
This paper discusses the aspect of student support that emerged as a key component of a longitudinal study into the experiences of nurses studying through open learning in the UK. Students engaged in this study were mature learners who were practicing nurses and predominantly, but not exclusively, women. Participants perceived entering higher education as a considerable challenge.